Karakteristik Kue â€œLekunâ€ Khas Maumere Timur Ditinjau Dari Jenis Kemasan Dan Lama Penyimpanan - Maria Intan Claudia Yatub; A A Made Semariyani; Ni Made Ayu Suardani Singapurwa (Fakultas Pertanian, Universitas Warmadewa, 2021)
â€œLekunâ€ cake is a traditional East Maumere cake that is specially made during engagement ceremonies to weddings or mourning ceremonies (Lodo Huer). â€œLekunâ€ cake has the potential to be used as souvenirs at this time. However, the